HIGH CLASS WOMEN IN SOCCER: THEIR REPRESENTATION ABOUT THIS PRACTICE (Fiep Bulletin - online, 2013)
This document evidences the participation of women in practical of soccer, having as it shows a group of 17 women, young and adults, who carry through the activity two times per week, in a private high class club in the City of Nova Iguaçu, Baixada Fluminense, state of Rio de Janeiro. The objective is to identify and to analyze the motivations that take women of these social class to practice this sport said popular in our country, the easiness's that they find and the difficulties they confront. The methodology consisted of participant comment, interviews of the elite, and press conference with the focal group, aid of the critical theories of analysis of the speech. The results evidence that the participation of the women of high class in the soccer constitutes evidence against the hypothesis that the soccer is sport of masculine reserve.
Keywords: feminine soccer; social representation; adversities